A fine summer's day - Todd, Charles (Todd, Charles. Inspector Ian Rutledge novels, 2015)
"New York Times bestselling author Charles Todd takes readers on a trip to Ian Rutledge's past, with the story of the last case the Scotland Yard detective tackles before he goes off to fight in World War I"--